Models of currency crises with banking sector and imperfectly competitive labor markets - Jian-Guang Shen (Bank of Finland, 2001)
This study extends the standard currency crisis theory (especially the second-generation models) by adding and emphasizing strategic interactions of agents in anticipating currency crises.The models in this study have a fairly elaborate and extensive micro-based structure, covering the household, firm, bank and central bank. Domestic interest rates are determined in a Stackelberg game where the bank is the leader and the firm the follower.The central bank's exchange rate decision is a function of private sector expectations on the exchange rate and international interest rates. Under certain world interest rates the pegged exchange rate can be sustained, as domestic fundamentals are compatible with the external monetary environment.Under other world interest rates, varying expectations on exchange rates can result in more than one equilibrium exchange rate.In addition, the higher the world interest rate, the higher the equilibrium devaluation rate. In the latter part of the study, the wage rate is endogenously determined in a bargaining framework and fiscal policy in the form of infrastructure investment is introduced.The interaction between fiscal policy and the wage bargaining process is incorporated into the basic model framework.The trade union's bargaining power and marginal labor disutility, as well as fiscal expenditure can also play a role in the exchange rate policy.The different time sequence of actions of the trade union and business sector makes a difference in the equilibrium exchange rates.Under certain conditions, the interaction between trade union and fiscal authority can break the 'wage-devaluation' spiral.
URN:NBN:fi:bof-201408071704
Keywords: 330; currency crisis; banking sector; Stackelberg game; wage bargaining; the Finnish crisis.